2011
DOI: 10.1111/j.1365-2184.2011.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumour and anti-angiogenetic effects of zoledronic acid on human non-small-cell lung cancer cell line

Abstract: Taken together, these results support a possible anti-cancer and anti-angiogenetic activity of Zol. Our data may not only provide a basis for the clinical use of this drug as preventive agent of bone metastases but also suggest that Zol deserves attention as an anti-cancer agent in non-small-cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 36 publications
3
48
0
1
Order By: Relevance
“…According to previous studies, it is controversial whether ZOL affects cyclin and cyclin-dependent kinase inhibitor expression levels in cancer cells (14,(25)(26)(27). To elucidate the mechanism by which ZOL causes S-phase arrest in CNE-2 and HNE-1 cells, the expression status of cyclins A, B, D1 and E, as well as p21 CIP1 and p27…”
Section: Zol Plus Ir Elevates the Expression Levels Of S-and M-phase mentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, it is controversial whether ZOL affects cyclin and cyclin-dependent kinase inhibitor expression levels in cancer cells (14,(25)(26)(27). To elucidate the mechanism by which ZOL causes S-phase arrest in CNE-2 and HNE-1 cells, the expression status of cyclins A, B, D1 and E, as well as p21 CIP1 and p27…”
Section: Zol Plus Ir Elevates the Expression Levels Of S-and M-phase mentioning
confidence: 99%
“…This effect of ZOL could be observed on cancer cells derived from a variety of tumors, including breast, prostate and pancreatic cancers, by inducing cell apoptosis and inhibiting cell invasion, adhesion and angiogenesis (10)(11)(12)(13). Currently, numerous patients with bone metastases secondary to a broad range of solid tumors are benefiting from the antitumor effects of ZOL (14).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that ZOL exhibited indirect antiangiogenetic effects by suppressing the vascular endothelial growth factor (VEGF) expression in cancer cells, in a dose-dependent manner (Di Salvatore et al 2011). …”
Section: Zol Suppresses Vegf Expression In Combination With Irmentioning
confidence: 99%
“…The mechanism involves inhibition of farnesyl pyrophosphate (FPP) synthase function in the mevalonate pathway, and it inhibits the activity of osteoclasts and induces osteoclast apoptosis (9,10). ZA has shown antitumor effects in many tumor cells, including NSCLC (11,12). Meanwhile, it can increase the antitumor effects in combination with chemotherapy and radiotherapy (13,14).…”
Section: Introductionmentioning
confidence: 99%